The Influence of Organizational Climate and Motivation on Employee Performance at The District Health Office Garut - Firmansyah, Yusuf; Ridwan, S; Roswinna, Winna (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The purpose of this study was to determine and analyze (1) organizational climate; (2) work motivation; (3) employee performance; (4) the effect of organizational climate and motivation on employee performance at the Garut Regency Health Office, both simultaneously and partially. The method used in this research is in accordance with the expected objectives, namely descriptive and verification methods. The unit of analysis in this study was the employees of the Garut Regency Health Office, with a sample of 51 people and the analysis method used is frequency distribution and path analysis. Based on the results of the analysis, it is found that the Organizational climate at the Garut Regency Health Office is quite conducive; employees of the Garut Regency Health Office have a high level of motivation; employees of the Garut Regency Health Office have a high performance. Employees of the Garut Regency Health Office have a fairly high performance and organizational climate and motivation affect the performance of employees of the Garut Regency Health Office. However, when viewed partially, it turns out that organizational climate is more dominant in influencing employee performance than motivation. Organizational climate dominantly influences employee performance rather than motivation, therefore the Garut Regency Health Office is required to prioritize improvements in the organizational climate of employees by carrying out continuous bureaucratic reform.